Щиповки комплекса Cobitis elongatoides-taenia (Cypriniformes, Cobitidae) Северо-Западного Причерноморья как модель филогеографических построений - Межжерин, С.В.; Павленко, Л.И.; Роженко, Н.В.; Верлатый, Д.Б. (Видавничий дім "Академперіодика" НАН України, 2007)
Biochemical genetic investigation and cytometric analysis from diploid-polyploid spined loaches associations of lower reaches of the rivers of Danube, Dniester, and Dnieper found substantial distinctions of their genetic structure and, consequently, certain historical isolations and, in case with Dniester, the uniqueness of the population consisting exceptionally of individuals of hybrid polyploid biotypes. Thus, in all basins, polyploid specimens only of the Danube origin are found. Diploid species of Danube (С. elongatoides, C. ''tanaitica'') have not contained introgressive genes and have autochthonous origin, while the diploid form predominating in lower Dnieper basin has genes not less than three allospecies of C. (superspecies) taenia with predominance of genes of C. (taenia) taenia and, consequently, has adventure nature de bene esse.